MODELLING DISTRIBUTION OF CONTAMINATING SUBSTANCES OF ELECTRIC POWER EMISSIONS IN THE ATMOSPHERE ON THE BASIS OF THE SKAT PROGRAMMING COMPLEX - Aleksandra M. Antonova (Известия Томского политехнического университета: Инжиниринг георесурсов, 2019)
Relevance of the research lies in the necessity of accuracy improvement of independent assessments at forecasting the content of pollutants in the air emitted by energy facilities, including nuclear power plants. The aim of the research is justifying the choice of a method for calculating the gaseous pollutant distribution from continuously operating sources located at high altitude with consideration of meteorological factors and operation test of the software package. Objects of the research are the method of calculating the dispersion of gaseous pollutants МRR-2017 and the Pasquill method for calculating pollution from a continuously operating high source under various steady meteorological conditions. Methods: simulation and computational analysis based on the developed computer software complex «SKAT». Results. Methods for dispersion of gaseous pollutants in the atmosphere: МRR-2017 and Pasquill were analyzed. It was concluded that the Pasquill method based on the Gauss model is preferable for calculating the distribution of gaseous pollutants emitted by energy facilities at various atmospheric conditions of steady meteorological factors. The developed software package «SKAT» can be used to predict pollutant concentration values near the earth surface and calculate dispersion of pollutants in the atmospheric air when solving the problems of monitoring emissions of pollutants in the presence of currently operating enterprises. Using the Gauss model the authors have studied the distribution of the emitted radionuclides concentration in the atmospheric layer next to the earth surface coursed by the designed power unit with the BREST-300 reactor and the on-site nuclear fuel cycle for conditions of Seversk city, Tomsk Region.